(3JOejQ GdYQGb HYO (B139 (3jheG ef GdeHGOQGJ h GdeSGYj GdOhdjI(B/s - (3QjJTGQO HGjdj s; (3YHO GdhgGH eMeO GdRfJGfjs ((3GdbGgQI(B:s (3GdOGQ GdLeGgjQjI ,s, 1993)
(3jMJhj Ydi edNU U (B209 -218s
. 240-220 (3HHdjhLQGajG(B: (3UaMGJ(B.s
Keywords: (3GdUQGY GdOhdj s